“There’s only one pot of money it can come from”: A Corpus-Based Analysis of the International Baccalaureate in Canada’s Provinces - Fitzgerald, Saira (Canadian Journal of Education/Revue canadienne de l’éducation, 2020)
This study has a dual purpose: (1) to show how computer-assisted discourse analysis of a 1.5-million-word specialized corpus can uncover patterns of language use that provide insights into the beliefs and values of a particular social group, making possible a “new way of looking at old puzzles” (Stubbs, 2010); and (2) to examine how the International Baccalaureate (IB) is represented in the Canadian provincial context. Although keywords reveal lexical differences in how the IB is represented in each province, in-depth contextual analysis indicates a similarity of concerns, particularly with regard to funding and cost of IB programs. Keywords: International Baccalaureate, corpus linguistics, discourse analysis, keyword analysis, education funding, policy, media